PENGARUH NANOPARTIKEL ZINC OXIDE DAN ETILEN GLIKOL TERHADAP SIFAT FISIK DAN ANTIMIKROBA BIODEGRADABLE FOAM - Risma Rahmatunisa; Evi Savitri Iriani; Nugraha Edhi Suyatma; Rizal Syarief (Jurnal Penelitian Pascapanen Pertanian, 2015)
Biodegradable foam packaging were made from tapioca, corn hominy, zinc oxide nanoparticles (ZnONP), and plasticizer ethyleneglicol (EG). Packaging materials were processed by thermopressing. The aim of research was to find out the effects of ZnONP andEG addition. The research design was a completely randomized factorial followed by Duncan test at α=5%. Two factors used in theresearch, namely ZnONP concentrationsat 0, 1, and 2 % and EG concentrations at 0 and 5%. The effects of ZnONP incorporation onphysical properties and antimicrobial activity of the trays were evaluated by analysis on their color parameters, moisture content, water absorption, density, crystallinity, morphological structure, thermal and antimicrobial activity. The best treatment was Z2P0 with 2% ZnONP and 0% EG, characteristics of biodegradable was L value 78.42, °hue value 91.88, moisture content 7.65%, water absorption59.65%, density 0.64g/cm³, crystallinity 38.3%, Tm 160.24°C, and reduced 1 log of Staphylococcus aureus colonies. The researchproved that the obtained biodegradable foam made from tapioca, corn hominy, ZnONP, and plasticizer EG has a potential to be used asantimicrobial packaging for food products.